The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.ejvs.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Stent Graft Repair is an Effective and Safe Alternative Therapy for Arteriovenous Graft Pseudoaneurysms

Abstract: The study demonstrates that endovascular stent graft repair is an effective and safe alternative therapy for AVG pseudoaneurysms. However, the rate of thrombosis and infection was high and needs to be balanced against open surgery in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…In our experience, the Bard Lifestent ® (Bard Medical) can be difficult to puncture as it may collapse with needling. Covered selfexpanding stents in the AVF, which have been previously reported, 31 may protect against post-procedure limb bruising observed in this study. However, the optimal choice of stent is at present subject to further study.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In our experience, the Bard Lifestent ® (Bard Medical) can be difficult to puncture as it may collapse with needling. Covered selfexpanding stents in the AVF, which have been previously reported, 31 may protect against post-procedure limb bruising observed in this study. However, the optimal choice of stent is at present subject to further study.…”
Section: Discussionsupporting
confidence: 66%
“…Although AVF stent infection has been recorded in the literature, 33 these remain rarely reported, with emerging reports of successful use of stents for cannulation without a significantly increased risk of infection, stent fracture or protrusion through the skin. 31 The previously described use of plain balloon angioplasty and tributary ligation 9 may enlarge the conduit and thus facilitate access. The addition of a stent allows the resulting lumen to be scaffolded, which we have found improves the ability to palpate the conduit.…”
Section: Discussionmentioning
confidence: 99%
“…2,10 However, a high risk of thrombosis and infection has been reported in the covered stent grafts when used for exclusion of pseudoaneurysm especially in patients using prosthetic access grafts ranging from 11 to 35%. 4,14,15 The K-DOQI guidelines recommend open surgical repair with surgical resection and interposition graft especially when the pseudoaneurysm is infected, twice the diameter of the graft, threatens the overlying skin, or is rapidly increasing in size with signs of impending rupture. 7 Our focus in the current study was thus to determine the clinical safety and efficacy of endovascular stent graft repair in pseudoaneurysms with signs of infection and bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Though open surgical repair still remains the current standard of treatment as per the K-DOQI guidelines, recent literatures have focused on the clinical safety and efficacy of endovascular stent graft intervention for the management and exclusion of pseudoaneurysms complicating hemodialysis access. 2,[4][5][6] A recent study by Wong et al in 35 patients showed 100% technical success rate with 37 endovascular stent graft repairs to exclude AVG pseudoaneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…Which one of the following interventions below is most appropriate? 3 A. Immediate ligation of the arteriovenous graft with concurrent tunneled dialysis catheter insertion with a schedule of new access creation 6 weeks later.…”
mentioning
confidence: 99%